Risk factors and injury mechanism in Triathlon - Migliorini, S. (Journal of Human Sport & Exercise, 2011)
In the triathlon the combined practice of swimming, cycling and running permits the reduction of overuse injuries compared to the practice of the running alone. Redistribution of stress over several part of the body and correction of muscle imbalance are cited as reasons for the reduction in injuries occurrence. Nonetheless, like other endurance sports, 80-85% of triathlon injuries can be scribed to overuse. From an etiopathogenetic point of view the overuse injuries must be studied in relation to the technical characteristics of the triathlon, to the transitional phases between the disciplines and particularly to the cycle-run transition, to the different load of training that the preparation of the Olympic distance requires compared to the long distance triathlon. Most of the injuries are caused by running and athletes most at risk are former swimmers and cyclists, since they lack of running experience and muscle elasticity. The triathlon cycle-run transition (T2) is a period of particular risk for knee and lower back injury. The knee, the ankle/foot and the lower back are the anatomic site most at risk of injuries. Ileotibial band friction syndrome is common in age groupers whereas Achilles tendon injuries and stress fractures occur more in elite athletes. Previous injuries are correlated with injuries occurrence and the sudden changes in training intensity or volume, hill training and the insufficient development of running technical ability are injuries extrinsic factors. The acute traumatology is due almost exclusively to falls in training and competition in cycling. The episodes of rhabdomiolysis are instead not rare, associated or not to exertional heat/idratation injuries. Injury prevention is based in particular on the learning of the correct technique of the three disciplines, on the right programming of the training sessions, on the study of the overload that the biomechanics of the transition phases between the three sports act on the locomotor apparatus and on the suitability of the technical instruments used.